Synergetic Approach to the Educational Process in the Discourse of Contemporary Educational Research - Iryna Slonevska; Svitlana Piroshenko (Pedagogical Discourse, 2015)
The article analyzes the methodological potential synergistic approach to the educational process in the discourse of contemporary educational research. It is argued that the nomination as the modern paradigm of new forms of synergistic integration and system approaches actualizes the research of the content and nature of changes occurring in modern science. Nowadays the review of research sources gives reason to believe that this is the way educational paradigm transformation forms a modern pedagogy image on Postnonclassical stage of its development. Attention is focused on traditional relationships of classical concept of pedagogy and synergetic paradigm of educational process. Thus, it is stressed that the modernist paradigm of educational process is focused on achieving a complete, comprehensive concept of systematic, consistency, totality, stability; in it’s turn, postmodern paradigm is focused on achieving and maintaining abnormalities, plurality, chaos. It is concluded, that modern education content is generally viewed as means of a personal development, not as a goal of schooling itself. Development and solution of educational problems is based on the application of the principles of synergy in the humanitarian field. Teaching process is understood as a complex conglomerate, characterized by multidimensionality and multivalency. Thus, synergetic educational paradigm is quite natural for Postnonclassical philosophical and general discourse and arose in response to the crisis of stereotypical, linear and mechanistic thinking.